Is small intestinal bacterial overgrowth a cause of hyperdynamic circulation in cirrhosis? - Maslennikov, Roman; Pavlov, Chavdar; Ivashkin, Vladimir (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Small intestinal bacterial overgrowth (SIBO) and hemodynamic changes are common in cirrhosis. We wanted to examine our hypothesis whether SIBO leads to hemodynamic changes in cirrhosis. Materials and Methods: A total of 50 patients with cirrhosis and 15 healthy controls were enrolled in a pilot prospective study. All participants underwent the lactulose hydrogen breath test for SIBO and echocardiography with a simultaneous assessment of blood pressure and heart rate. Cardiac output and systemic vascular resistance were calculated. Results: Study participants with SIBO had a lower systolic blood pressure and systemic vascular resistance compared to those without SIBO and to healthy controls (110.2±12.3 mmHg vs. 126.2±21.0 mmHg and 121.2±9.8 mmHg; p=0.005 and p=0.011, respectively; 1312±352 dyn•s•cm−5 vs. 1704±424 dyn•s•cm−5 and 1648±272 dyn•s•cm−5; p=0.001 and p=0.006, respectively), but a higher cardiac output (5.38±1.41 l/min vs. 4.52±1.03 l/min and 4.40±0.68 l/min; p=0.034 and p=0.041, respectively) and C-reactive protein (10.5[1.2-16.5] mg/l vs. 2.8[0.6-9.1] mg/l; p=0.028; no comparison with healthy controls). There were no significant differences between patients without SIBO and healthy controls with regard to systolic blood pressure (p=0.554), systemic vascular resistance (p=0.874), and cardiac output (p=0.795). SIBO was associated with vasodilation and hyperdynamic circulation in decompensated cirrhosis (p=0.002; p=0.012), but not in compensated cirrhosis (p=1.000; p=0.474). Conclusions: SIBO is associated with hyperdynamic circulation and other hemodynamic changes in cirrhosis and may be a principal factor causing these through systemic inflammation.